Don't start a smoking prevention campaign - Cembrano, Leah Michelle L. (2013)
Smoking is one of the three major risk factors of cardiovascular disease, cancer and other respiratory illnesses, which make up 60 percent of all the deaths in the country.? ?Worldwide, tobacco use causes more than 5million deaths per year, and current trends show that tobacco use will cause more than 8 million deaths annually by 2030.? It is obvious that a lot of people are suffering from diseases attributed to smoking despite the fact that it is preventable. Despite the fact that people are aware of the consequences of smoking, and that several anti-smoking campagins are present, people still decide to smoke. Through data gathering from different sources such as books, articles, and personal interviews, more information about the reasons behind why people start to smoke, and why they decide to continue to smoke despite being aware about the negative effects. The researcher was also able to learn more about the current anti-smoking efforts which are present, along with how people reacted to these efforts. Based on the feedback given by the interviewees, the researcher was able to adjust accordingly to make the effort more suitable to the target audience, and possibly making it more effective.
"April 2013."
Thesis (BFA)--University of the Philippines, Diliman.
Keywords: Cigar smoking -- Philippines